PENGARUH MOTIVASI TERHADAP KINERJA GURU DIMODERASI OLEH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA SEKOLAH - Hartatik, Sri (Students Journal of Economic and Management, 2012)
The purpose of this study was to examine and analyze the effect of motivation on teacher performance is moderated by the leadership of the Principal The study was conducted on all civil servant in UPTD Dikpora Sayung Demak district, with a minimum working period of 6 years with a sample 167 respondents. Data sources are the primary data and sample measurement using a Likert scale with five alternative answers. This research in the form of explanatory research that aims to prove the analysis of all the variables studied. Motivation positive and significant effect on the performance of elementary school teachers Sayung District Demak regency. Leadership of the principal negative effect on the performance of elementary school teachers in the district Sayung Demak regency. School culture positive and significant effect on the performance of elementary school teachers in the district Sayung Demak regency. Leadership moderate motivation with teacher performance and a significant positive effect on the performance of elementary school teachers in the district Sayung Demak regency. School culture moderates the motivation with teacher performance negatively. Keywords: motivation, leadership principals, school culture and teacher performance